Activation of Dopaminergic D2/D3 Receptors Modulates Dorsoventral Connectivity in the Hippocampus and Reverses the Impairment of Working Memory after Nerve Injury - Helder Cardoso-Cruz (2014)
Dopamine plays an important role in several forms of synaptic plasticity in the hippocampus, a crucial brain structure for working memory (WM) functioning. In this study, we evaluated whether the working-memory impairment characteristic of animal models of chronic pain is dependent on hippocampal dopaminergic signaling. To address this issue, we implanted multichannel arrays of electrodes in the dorsal and ventral hippocampal CA1 region of rats and recorded the neuronal activity during a food-reinforced spatial WM task of trajectory alternation. Within-subject behavioral performance and patterns of dorsoventral neuronal activity were assessed before and after the onset of persistent neuropathic pain using the Spared Nerve Injury (SNI) model of neuropathic pain. Our results show that the peripheral nerve lesion caused a disruption in WM and in hippocampus spike activity and that this disruption was reversed by the systemic administration of the dopamine D2/D3 receptor agonist quinpirole (0.05 mg/kg). In SNI animals, the administration of quinpirole restored both the performance-related and the task-related spike activity to the normal range characteristic of naive animals, whereas quinpirole in sham animals caused the opposite effect. Quinpirole also reversed the abnormally low levels of hippocampus dorsoventral connectivity and phase coherence. Together with our finding of changes in gene expression of dopamine receptors and modulators after the onset of the nerve injury model, these results suggest that disruption of the dopaminergic balance in the hippocampus may be crucial for the clinical neurological and cognitive deficits observed in patients with painful syndromes.